2019
DOI: 10.1308/rcsann.2019.0022
|View full text |Cite
|
Sign up to set email alerts
|

Straight-to-test for the two-week-wait colorectal cancer pathway under the updated NICE guidelines reduces time to cancer diagnosis and treatment

Abstract: Introduction The 2015 National Institute for Health and Care Excellence guidelines widened the referral criteria for the two-week-wait pathway for suspected lower gastrointestinal cancer. We implemented a straight-to-test protocol to accommodate the anticipated increase in referrals. We evaluated the impact of these changes for relevant pathway metrics and clinical outcomes using a retrospective cohort study with historic controls. Materials and methods We analysed data from all patients referred to a teaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…This study confirms better cancer detection rates comparable to straight-to-test models 17 , 24 , 25 , 27 , 28 and exceeds many 2WW pathways. 39 , 40 Only 16% of new cancers fulfil a 2WW referral criteria. This highlights the difficulty for GPs to identify the appropriate referral route and the importance of a vague symptom pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This study confirms better cancer detection rates comparable to straight-to-test models 17 , 24 , 25 , 27 , 28 and exceeds many 2WW pathways. 39 , 40 Only 16% of new cancers fulfil a 2WW referral criteria. This highlights the difficulty for GPs to identify the appropriate referral route and the importance of a vague symptom pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a pathway variation was apparent, with some patients gaining direct access to testing, whilst others were surprised by initial specialist appointments before being sent for tests. This has also been identified in an endoscopy patient experience study 58 and highlights a potential area for improvement, as previous literature has identified that a straight‐to‐test protocol results in a reduction in times to cancer diagnosis and cancer treatment 59,60 . In addition, GP direct access testing performed as well as, and on some measures better than, consultant‐triaged testing on measures of disease detection, appropriateness of referrals, interval from referral to testing, and patient and GP satisfaction 61 …”
Section: Discussionmentioning
confidence: 66%
“…This has also been identified in an endoscopy patient experience study 58 and highlights a potential area for improvement, as previous literature has identified that a straight-to-test protocol results in a reduction in times to cancer diagnosis and cancer treatment. 59,60 In addition, GP direct access testing performed as well as, and on some measures better than, consultant-triaged testing on measures of disease detection, appropriateness of referrals, interval from referral to testing, and patient and GP satisfaction. 61 At the referral stage, whilst health-care professionals may not want to create unnecessary anxiety for patients, previous research suggests fear can actually be increased if the patient feels unclear or unprepared for the cancer referral pathway.…”
Section: Comparison To Previous Researchmentioning
confidence: 99%
“…The clear benefits of STT cancer pathways have been reported in many studies. 21 , 22 , 23 The only published data specific to implementing a STT CTC service for symptomatic colorectal patients is from Leicester General Hospital. 21 This pathway was offered to all patients >60 years with an CIBH and iron-deficiency anaemia (IDA), and in 12 months, 1,792 STT CTC examinations were performed.…”
Section: Discussionmentioning
confidence: 99%